MENINGKATKAN KEMAMPUAN SISWA PADA MATERI INTRODUCING SELF MELALUI MODEL THINK PAIR SHARE DI KELAS IV SDN 7 BILUHU KABUPATEN GORONTALO - WIWY T PULUKADANG (JAMBURA Elementary Education Journal, 2021)
Abstrak This study intends to make improvements to the learning process through think pair share model to improve the student’ abilities of introducing self in class IV at SDN 7 Biluhu. This study used a classroom action research with research procedures through the preparation, action, observation and evaluation, also analysis and reflection. Indicator performance defined is an increase in the ability of 70% of students about introducing self through think pair share model. Based on the data obtained from the study conducted at the beginning of observation, only 6 people or 30% of the 20 students who achieve value what has been set. Learning first cycle after obtaining the action through a model think pair share, of the 20 students, there are 11 people or 55% increase, and in the second cycle of learning has increased a total of 18 or 90% of students achieve mastery and performance indicators are also defined. Based on these studies, it can be concluded that the use of think pair share model can improve student’ abilities of introducing self at class IV at SDN 7 Biluhu.